2016
DOI: 10.3390/w8050171
|View full text |Cite
|
Sign up to set email alerts
|

Climate Variability and Groundwater Response: A Case Study in Burkina Faso (West Africa)

Abstract: West Africa experiences great climate variability, as shown by the long-lasting drought since the 1970s. The impacts of the drought on surface water resources are well documented but remain less studied regarding groundwater resources. The nexus between climate variability and groundwater level fluctuations is poorly documented in this area. The present study focuses on the large reserve of groundwater held by the Kou catchment, a tributary of Mouhoun river (formerly the Black Volta) in the southwest of Burkin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 54 publications
1
17
0
Order By: Relevance
“…Also, the West African countries have been experiencing huge climate variability in the last decades with direct impact in the groundwater (Tirogo et al, 2016), although it has been shown a resilience for shortterm inter-annual variation (Lapworth et al, 2013). Climate variability has also been verified by differences on tree-rings along countries such as Ivory Coast (de Ridder et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Also, the West African countries have been experiencing huge climate variability in the last decades with direct impact in the groundwater (Tirogo et al, 2016), although it has been shown a resilience for shortterm inter-annual variation (Lapworth et al, 2013). Climate variability has also been verified by differences on tree-rings along countries such as Ivory Coast (de Ridder et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Abdullahi et al (2015) identified both significant positive and negative trends for the north-eastern region of Peninsula Malaysia for different time periods, suggesting overall trends across an entire sampling period may mask significant trends within distinct climatic phases. Similarly, Tirogo et al (2016) found different significant MK groundwater trends in multi-year climatic phases in West Africa. These studies suggest that an approach that includes overall trend analysis and trend analysis within distinct climatic phases may provide more insightful information about potentially stressed groundwater systems.…”
Section: Introductionmentioning
confidence: 86%
“…For subbasin 5, the driest subbasin, the value of of GW_DELAY was increased by 53.05 days. In addition, other hydrogeological conditions also contribute to the flow of groundwater, such as transmissivity and storage coefficient indicated in the work of Tirogo et al (2016) in Burkina Faso in West Africa.…”
Section: Calibration Of the Modelmentioning
confidence: 99%